70 Improving the Documentation of DNACPR Decisions Following the Transition to Electronic Record Keeping. (16th March 2021) - Jackson, L; Saund, J; Donnelly, G
Abstract: Background: This quality improvement project was based at The Royal Bolton Hospital across our four Complex Care wards. Introduction: We have recently transferred to electronic record keeping. At these points of transition there may be an adverse impact on the quality of patient care and safety. We recognised on our own ward there were inaccuracies between the required paper form and electronic documentation of DNACPR decisions. Consequently, we wanted to review and improve the accuracy of our DNACPR documentation to ensure safe and effective patient care. Methods: To gauge the scope of the problem we audited 87 patient's electronic and paper notes, with no exclusion criteria. We reviewed whether each patient had a formal resuscitation decision, and if a DNACPR decision had been made whether we met our hospital policy by having: a paper DNACPR form in the correct patient's notes a documented electronic decision (on the daily ward round proforma) an electronic "Resuscitation and treatment escalation plan" 93% of the 87 patient's had an active decision regarding resuscitation, with a DNACPR decision documented for 50 patients. Of these 50 patients only 11 had all three forms of documentation. More worryingly, there were discrepancies in the documented DNACPR decisions for 11 patients across paper and electronic records. Interventions: We escalated our concerns to the Clinical Governance team who sent out a trust wide SBAR highlighting this as an urgent clinical issue. On a directorate level we incorporated DNACPR decision documentation into our afternoon safety huddle and arranged informal teaching for medical, nursing and administrative staff. Results: Reassuringly, the subsequent re-audit of 90 patient's notes showed only one patient to have a discrepancy between paper and electronic documentation. We saw an improvement to 98% having paper forms in the right bedside notes and 100% having a documented electronic DNACPR decision. Conclusion: Through local education and trust-wide dissemination of our expected standards we have seen some improvement. We recognise the importance of maintaining this, and importantly that there is still work to be done. The electronic "Resuscitation and treatment escalation plan" is still rarely completed and provides important information on escalation of care and thus will be the focus of a further educational intervention.